2018
DOI: 10.1111/sms.13058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐impact exercise on the physical properties of bones of ovariectomized rats fed to a high‐protein diet

Abstract: The aim of this study was to evaluate the effects of high-impact physical exercise as a prophylactic and therapeutic means in osteopenic bones of rats submitted to ovariectomy and protein diet intake. A total of 64 Wistar rats were divided into eight groups (n = 8 each), being: OVX, ovx, standard diet and sedentary; OVXE, ovx, standard diet and jump; OVXP, ovx, high-protein diet and sedentary; and OVXEP, ovx, high-protein diet and jump; SH, sham, standard diet and sedentary; SHE, sham, standard diet and jump; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The main consequence of such diet was that it impaired femoral mechanical and densitometric properties. The bone tissue is composed of around one third of proteins [23], which influences bone mineral content [9]. Indeed, while a protein-based diet has been positively associated with bone quality [24][25][26][27], the reduction of protein intake has been associated with increased risk for osteoporosis [26,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main consequence of such diet was that it impaired femoral mechanical and densitometric properties. The bone tissue is composed of around one third of proteins [23], which influences bone mineral content [9]. Indeed, while a protein-based diet has been positively associated with bone quality [24][25][26][27], the reduction of protein intake has been associated with increased risk for osteoporosis [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been indicated for the prevention and non-pharmacological treatment of osteopenia and osteoporosis, as it generates necessary mechanical osteogenic stimuli with few side effects 9. Studies have demonstrated that systematic physical exercises can improve bone properties such as strength, bone mineral content and density [9,10]. Furthermore, it is indicated that physical activities performed in the childhood and adolescence favor the accumulation of minerals in the bones and contribute to the bone health in the adulthood [11].…”
Section: Introductionmentioning
confidence: 99%
“…The left femora were submitted to densitometric analysis using “dual-energy” x-ray densitometer equipment, Alpha, Lunar DPX ® (Lunar, Madison, WI, United States) installed at the School of Medicine of Ribeirao Preto. Adapted for measurement small animals with the PIXImus software (Lunar, Madison, WI, United States) 49,50 . The image acquisition is proceeded with the femurs (distal portion of the femur) position with ROI of 9 mm² (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The software used for statistical analysis was SPSS 20.0 (IBM, New York, NY, USA) and the samples were submitted to the general linear model test, and all comparisons were submitted to Bonferroni adjustment 24,49 . Analysis of TRAP were subjected to normality test and then it was subjected to nonparametric test with Kruskal Wallis as analysis of variance, with a post-test of Dunn that was held to specify these differences.…”
Section: Methodsmentioning
confidence: 99%